Utilization of YouTube-Based Audio Visual Learning Media in Improving Indonesian Language Learning Outcomes for Class V (Phase C) UPTD SDN 35 BARRU Students - Agus, M.; Irbar, Nur Afmi; Safika, Safika; Japar, Wahyudi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Using appropriate learning media is one of the keys to the success of the teaching and learning process. This article discusses the use of YouTube-based audio-visual media in improving Indonesian language learning outcomes for class V students at UPTD SDN 35 Barru. YouTube-based media offers a variety of content that is interactive, interesting and easy to access so that it can increase students' learning motivation and make it easier to understand the material. This research uses the classroom action research (PTK) method with a qualitative approach to analyze the use of YouTube as a learning medium. The results of this research show that students who learn using YouTube-based media conclude that there is an increase in student learning outcomes.